2005
DOI: 10.1161/01.atv.0000183674.88817.fb
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Pregnane X Receptor in Mice Antagonizes the Cholic Acid–Mediated Changes in Plasma Lipoprotein Profile

Abstract: Objective-Modification of lipoprotein metabolism by bile acids has been mainly explained by activation of the farnesyl X receptor (FXR). The aim of the present study was to determine the relative contribution of the pregnane X receptor (PXR), another bile acid-activated nuclear receptor to changes in plasma lipoprotein profile. Methods and Results-Wild-type mice, Pxr-deficient mice, and Pxr-null mice expressing human PXR (Pxr-null SXR-Tg mice)were fed a cholic acid-containing diet, and consequences on plasma l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 46 publications
(43 reference statements)
2
19
0
1
Order By: Relevance
“…Our finding that rifampicinactivated PXR regulates HDL metabolism is consistent with a recent report that the induction of CYP3A4 is correlated with increased plasma HDL and apoA-I levels and that rifampicin and other PXR agonists increase apoA-I expression and serum HDL-cholesterol levels in rodents (33). Our results may suggest an indirect mechanism for the PXR regulation of HDL metabolism via the induction of CYP27A1 and activation of the LXRa target genes ABCA1 and ABCG1 in intestine cells (41).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding that rifampicinactivated PXR regulates HDL metabolism is consistent with a recent report that the induction of CYP3A4 is correlated with increased plasma HDL and apoA-I levels and that rifampicin and other PXR agonists increase apoA-I expression and serum HDL-cholesterol levels in rodents (33). Our results may suggest an indirect mechanism for the PXR regulation of HDL metabolism via the induction of CYP27A1 and activation of the LXRa target genes ABCA1 and ABCG1 in intestine cells (41).…”
Section: Discussionsupporting
confidence: 92%
“…Bile acids are known to reduce HDL cholesterol, plasma apoA-I, and hepatic apoA-I mRNA expression in wild-type mice (39,40). The inhibitory effect of bile acids is more pronounced in Pxr null mice and is attenuated in human PXR transgenic mice (41). It was suggested that PXR might antagonize the inhibitory effect of the bile acid receptor farnesoid X receptor on apoA-I mRNA expression and HDL metabolism and that bile acids may induce ABCA1 and ABCG1 gene transcription (42).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, were not reported. Interestingly, expression of human PXR in mice antagonizes cholic acid-mediated downregulation of plasma HDL levels and hepatic Apo-AI expression, which was attributed to repressed farnesyl X receptor activity by PXR ( 42 ). Albeit that different mechanisms may contribute to PXR-mediated effects on plasma lipid and lipoprotein levels in different animal models, all of this evidence suggests that activation of PXR can affect cholesterol metabolism and may play a role in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of Sirt1 regulation of PXR function [14] in xenobiotics metabolism is now required with important involvement of PXR in HDL cholesterol metabolism [124] [125]. Furthermore, the involvement of PXR in the diabetes has increased with the involvement of various PXR agonists in glucose and lipid dysregulation [126] [127].…”
Section: Endocrine Disruptors As Risk Factors For Obesity and Chronicmentioning
confidence: 99%